The ecological characteristics of mineral lick associated with animals in Belantikan Hulu Area, Central Kalimantan, Indonesia - Wicaksono, Gusti; Setia, Tatang Mitra; Yanuar, Achmad; Basalamah, Fitriah; Sapari, Iman (Generasi Biologi Indonesia, 2022)
Mineral licks are areas rich in essential minerals where wildlife such as mammals and birds frequent to lick or eat soil (geophagy). Mineral licks are a beneficial site for animals since the behavior increases mineral intake and emulsifies toxins that enter the digestive system. The Belantikan Hulu area is known to have mineral licks in its forest area, two of which are frequently visited by various animals. The purpose of this research is to provide an overview of the ecological characteristics of two different mineral licks, as well as to identify the diversity of animals that use the area. The study was carried out in the Belantikan Hulu area, using the capture and recapture method as well as the laboratory process to identify minerals in mineral licks. The results of the sample analysis revealed that the mineral licks in the two areas contain Na, K, Ca, and Mg. When compared to other locations, the Penggaraman area has the highest concentration of three minerals. During the research period, 2.133 independent photos were captured at two mineral lick sites. A total of 16 animal species were recorded, including 10 species of mammals and six species of birds. There is a symbiotic interaction of mutualism between mammals and birds at the mineral lick, as well as a sympathetic interaction in primates. The ecological characteristics of mineral licks, such as minerals and distance from human activity, affect wildlife visits to mineral lick sites.